2020
DOI: 10.22541/au.159434284.47529969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial patterns of leaf δ13C and δ15N of aquatic macrophytes in the arid zone of northwestern China

Abstract: The analysis of stable isotope composition is an important tool in research on plant physiological ecology. However, large-scale patterns of leaf stable isotopes for aquatic macrophytes have received considerably less attention. In this study, we examined the spatial pattern of the leaf δ13C and δ15N of macrophytes collected across the arid zone of northwestern China and tried to illustrate how they were affected by different environmental factors. Our results showed that the mean values of leaf δ13C and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Various factors of global change, including rising atmospheric CO 2 concentrations ([CO 2 ]) (Luo et al, 2004), early spring caused by global warming (Elmore et al, 2016), increased atmospheric N deposition (Fang et al, 2011; Hietz et al, 2011; Hiltbrunner et al, 2019; Pardo et al, 2006; Vallano & Sparks, 2013), and changes in patterns of precipitation (Craine et al, 2009; Pardo et al, 2006; Tang et al, 2021), have been identified directly or indirectly to affect foliar δ 15 N. For example, seasonality of precipitation and temperature can negatively affect foliar δ 15 N by influencing plant productivity, N input, soil microbial activities, and litter decomposition (Asseng et al, 2011; Gremer et al, 2018; Tang et al, 2021). Low precipitation and high potential evapotranspiration (PET) could increase denitrification‐driven N gas losses and decrease soil N leaching, thus increasing foliar δ 15 N (Gong et al, 2021; Houlton et al, 2006; Zhao et al, 2016). Increasing temperature might increase or decrease plant δ 15 N via stimulating N mineralization (increasing N supply, Craine et al, 2009; Pardo et al, 2006) or increasing plant growth (increasing N demand) due to prolonged growing season, respectively (Mason et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Various factors of global change, including rising atmospheric CO 2 concentrations ([CO 2 ]) (Luo et al, 2004), early spring caused by global warming (Elmore et al, 2016), increased atmospheric N deposition (Fang et al, 2011; Hietz et al, 2011; Hiltbrunner et al, 2019; Pardo et al, 2006; Vallano & Sparks, 2013), and changes in patterns of precipitation (Craine et al, 2009; Pardo et al, 2006; Tang et al, 2021), have been identified directly or indirectly to affect foliar δ 15 N. For example, seasonality of precipitation and temperature can negatively affect foliar δ 15 N by influencing plant productivity, N input, soil microbial activities, and litter decomposition (Asseng et al, 2011; Gremer et al, 2018; Tang et al, 2021). Low precipitation and high potential evapotranspiration (PET) could increase denitrification‐driven N gas losses and decrease soil N leaching, thus increasing foliar δ 15 N (Gong et al, 2021; Houlton et al, 2006; Zhao et al, 2016). Increasing temperature might increase or decrease plant δ 15 N via stimulating N mineralization (increasing N supply, Craine et al, 2009; Pardo et al, 2006) or increasing plant growth (increasing N demand) due to prolonged growing season, respectively (Mason et al, 2022).…”
Section: Introductionmentioning
confidence: 99%